2013
DOI: 10.1016/j.ajhg.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ANTXR1 Cause GAPO Syndrome

Abstract: The genetic cause of GAPO syndrome, a condition characterized by growth retardation, alopecia, pseudoanodontia, and progressive visual impairment, has not previously been identified. We studied four ethnically unrelated affected individuals and identified homozygous nonsense mutations (c.262C>T [p.Arg88*] and c.505C>T [p.Arg169*]) or splicing mutations (c.1435-12A>G [p.Gly479Phefs*119]) in ANTXR1, which encodes anthrax toxin receptor 1. The nonsense mutations predictably trigger nonsense-mediated mRNA decay, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 36 publications
0
74
0
Order By: Relevance
“…The craniofacial appearance in GAPO (G, growth retardation; A, alopecia; P, pseudoanodontia; O, optic atrophy) syndrome resembles that of CED [Demirgues et al, 2009]; however, unlike the above mentioned disorders GAPO has recently been found to be caused by defects in extracellular matrix regulation [Stránecký et al, 2013].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The craniofacial appearance in GAPO (G, growth retardation; A, alopecia; P, pseudoanodontia; O, optic atrophy) syndrome resembles that of CED [Demirgues et al, 2009]; however, unlike the above mentioned disorders GAPO has recently been found to be caused by defects in extracellular matrix regulation [Stránecký et al, 2013].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In Gorham-Stout disease, characterized by massive osteolysis and hemangiomatosis, VEGF secreted by osteoblasts may induce vascularization, while absence of nuclear VEGF most likely affects osteoblast differentiation [32]. Recent data demonstrated the role of tumor endothelial marker 8 (TEM8) in the pathophysiology of hemangiomas [33] and growth retardation, alopecia, pseudoanodontia, and optic atrophy (GAPO) syndrome [34] through regulation of VEGF signaling in endothelial cells. TEM8 forms a complex with VEGFR2 in endothelial cells and inhibits transcription of VEGFR1, thus protecting the cells from excessive signaling.…”
Section: Vasculature -Olsenmentioning
confidence: 98%
“…While our exome sequencing work was in progress, homozygous mutations in ANTXR1 located on chromosome 2p13.3 were described to be causative for GAPO syndrome [Stranecky et al, 2013]. Immunofluorescence analysis of cultured skin fibroblasts collected from GAPO cases demonstrated an aberrant pattern of actin cytoskeletal microfilament organization.…”
Section: Introductionmentioning
confidence: 99%